Design of monolithic compliant mechanisms with beam elements of distributed stiffness: Gestaltung monolithischer, verformbarer Mechanismen mit Stabelementen verteilter Steifigkeit. Issue 11 (17th November 2016) - Hanke, U.; Zichner, M.; Tudorache, A.; Modler, N.; Ashir, M.
Abstract : Lightweight structures made of fiber‐reinforced composites exhibit a considerable application potential for designing fully compliant monolithic mechanisms. The substitution of classical joints by flexible elements exhibits benefits in assembling these linkages. The inherently high ability for function integration and the specifically adjustable compliances offers the possibility to transmit motions only by structural deformations. Especially flexible beam elements with distributed stiffness enhance the synthesis of compliant mechanisms. With the predefined beam deflection with constant curvature, the adjusted material properties are directly defined without solving the Bernoulli – ordinary differential equation. The generalized synthesis of bistable monolithic compliant mechanisms deals with a three body system connected by three flexible elements by solving a two pose tasks.